Extremely short duration high-intensity training substantially improves endurance performance in triathletes - Jakeman, J.; Adamson, S.; Babraj, J. (Applied Physiology, Nutrition, and Metabolism, 2012)
High-intensity training (HIT) involving 30-s sprints is an effective training regimen to improve aerobic performance. We tested whether 6-s HITs can improve aerobic performance in triathletes. Six subelite triathletes (age, 40 ± 9 years; weight, 86 ± 11 kg; body mass index, 26 ± 3 kg·m-2) took part in cycle HIT and 6 endurance-trained subelite athletes (age, 36 ± 9 years; weight, 82 ± 11 kg; BMI, 26 ± 3 kg·m-2) maintained their normal training routine. Before and after 2 weeks of HIT, involving 10 × 6-s sprints or normal activity, participants performed a self-paced 10-km time trial and a time to exhaustion test on a cycle ergometer. Finger prick blood samples were taken throughout the time to exhaustion test to determine blood lactate concentration. Two weeks of HIT resulted in a 10% decrease in self-paced 10-km time trial (p = 0.03) but no significant change in time to exhaustion. The time taken to reach onset of blood lactate accumulation (OBLA, defined as the point where blood lactate reaches 4 mmol/L) was significantly increased following 2 weeks of HIT (p = 0.003). The change in time trial performance was correlated to the change in time taken to reach OBLA (R2 = 0.63; p = 0.001). We concluded that a very short duration HIT is a very effective training regimen to improve aerobic performance in subelite triathletes and this is associated with a delay in blood lactate build-up.